Acetyl-L-Carnitine downregulates invasion (CXCR4/CXCL12, MMP-9) and angiogenesis (VEGF, CXCL8) pathways in prostate cancer cells: rationale for prevention and interception strategies - Denisa Baci; Antonino Bruno; Caterina Cascini; Matteo Gallazzi; Lorenzo Mortara; Fausto Sessa; Giuseppe Pelosi; Adriana Albini; Douglas M. Noonan (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Prostate cancer (PCa) is a leading cause of cancer-related death in males worldwide. Exacerbated inflammation and angiogenesis have been largely demonstrated to contribute to PCa progression. Diverse naturally occurring compounds and dietary supplements are endowed with anti-oxidant, anti-inflammatory and anti-angiogenic activities, representing valid compounds to target the aberrant cytokine/chemokine production governing PCa progression and angiogenesis, in a chemopreventive setting. Using mass spectrometry analysis on serum samples of prostate cancer patients, we have previously found higher levels of carnitines in non-cancer individuals, suggesting a protective role. Here we investigated the ability of Acetyl-L-carnitine (ALCAR) to interfere with key functional properties of prostate cancer progression and angiogenesis in vitro and in vivo and identified target molecules modulated by ALCAR. Methods The chemopreventive/angiopreventive activities ALCAR were investigated in vitro on four different prostate cancer (PCa) cell lines (PC-3, DU-145, LNCaP, 22Rv1) and a benign prostatic hyperplasia (BPH) cell line. The effects of ALCAR on the induction of apoptosis and cell cycle arrest were investigated by flow cytometry (FC). Functional analysis of cell adhesion, migration and invasion (Boyden chambers) were performed. ALCAR modulation of surface antigen receptor (chemokines) and intracellular cytokine production was assessed by FC. The release of pro-angiogenic factors was detected by a multiplex immunoassay. The effects of ALCAR on PCa cell growth in vivo was investigated using tumour xenografts. Results We found that ALCAR reduces cell proliferation, induces apoptosis, hinders the production of pro inflammatory cytokines (TNF-α and IFN-γ) and of chemokines CCL2, CXCL12 and receptor CXCR4 involved in the chemotactic axis and impairs the adhesion, migration and invasion capabilities of PCa and BPH cells in vitro. ALCAR exerts angiopreventive activities on PCa by reducing production/release of pro angiogenic factors (VEGF, CXCL8, CCL2, angiogenin) and metalloprotease MMP-9. Exposure of endothelial cells to conditioned media from PCa cells, pre-treated with ALCAR, inhibited the expression of CXCR4, CXCR1, CXCR2 and CCR2 compared to those from untreated cells. Oral administration (drinking water) of ALCAR to mice xenografted with two different PCa cell lines, resulted in reduced tumour cell growth in vivo. Conclusions Our results highlight the capability of ALCAR to down-modulate growth, adhesion, migration and invasion of prostate cancer cells, by reducing the production of several crucial chemokines, cytokines and MMP9. ALCAR is a widely diffused dietary supplements and our findings provide a rational for studying ALCAR as a possible molecule for chemoprevention approaches in subjects at high risk to develop prostate cancer. We propose ALCAR as a new possible “repurposed agent’ for cancer prevention and interception, similar to aspirin, metformin or beta-blockers.